2017
DOI: 10.1186/s13068-017-0782-4
|View full text |Cite
|
Sign up to set email alerts
|

In muro deacetylation of xylan affects lignin properties and improves saccharification of aspen wood

Abstract: BackgroundLignocellulose from fast growing hardwood species is a preferred source of polysaccharides for advanced biofuels and “green” chemicals. However, the extensive acetylation of hardwood xylan hinders lignocellulose saccharification by obstructing enzymatic xylan hydrolysis and causing inhibitory acetic acid concentrations during microbial sugar fermentation. To optimize lignocellulose for cost-effective saccharification and biofuel production, an acetyl xylan esterase AnAXE1 from Aspergillus niger was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 39 publications
(74 reference statements)
10
63
1
Order By: Relevance
“…Diluted cDNA (20-30 times) was used for transcript analysis of transgenic plants. The expression was normalized to ubiquitin (Potri.005G198700) and tubulin (Potri.001G464400), and presented relative to the levels in the lowest-expressing line as previously described (Pawar et al, 2017a). The primers of reference and target genes are provided in Supplementary Table S1.…”
Section: Transcript Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…Diluted cDNA (20-30 times) was used for transcript analysis of transgenic plants. The expression was normalized to ubiquitin (Potri.005G198700) and tubulin (Potri.001G464400), and presented relative to the levels in the lowest-expressing line as previously described (Pawar et al, 2017a). The primers of reference and target genes are provided in Supplementary Table S1.…”
Section: Transcript Levelmentioning
confidence: 99%
“…These enzymes are grouped in at least eight Carbohydrate Esterase (CE) families that differ with regard to protein structure and other properties (Biely, 2012;Pawar et al, 2013). Previous studies have shown that introduction of an Aspergillus niger AXE1 (AnAXE1) from CE1 in Arabidopsis or in hybrid aspen and targeting the enzyme to the cell wall for post-synthetic xylan deacetylation significantly improved the cellulose digestibility without changing the growth properties of these plants (Pawar et al, 2016(Pawar et al, , 2017a. Post-synthetic xylan deacetylation was considered as a more promising strategy than synthetic xylan deacetylation in the Golgi, since the latter could induce excess glucuronidation (Donev et al, 2018) caused by the promiscuous activity of glucuronyl transferases GUX1 and GUX2 (Grantham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To engineer a reduction in xylan acetylation, an acetyl xylan esterase from the lignocellulosedegrading fungus Aspergillus niger (AnAXE1) was overexpressed in Arabidopsis (Figure 3) (Pawar et al, 2016). After observing beneficial effects, the same gene was used to generate transgenic overexpressors in hybrid aspen (Populus tremula L. × tremuloides Michx) (Pawar et al, 2017). The transgenic trees developed normally with approximately 10% less xylan acetylation.…”
Section: Xylanmentioning
confidence: 99%
“…Non-pressurized systems include water baths [64,66] and heat blocks [62,63], and typical temperatures are in the range 80-90 • C ( Table 2). Pressurized systems include autoclaves [61,67], ASE 350 Accelerated Solvent Extractor (Dionex, Sunnyvale, CA, USA) [68], Parr reactors (Parr Instrument Company, Moline, IL, USA) [65,69,70], single-mode microwave systems [54][55][56][57][58][59] (Table 2), and partially or fully automated robotic systems for 96-well plate format [46][47][48][49][50] (Table 2). One investigation has been based on transparent plastic microtiter plates for solvation of biomass using ionic liquids where biomass dissolution was determined by measuring scattered light [74].…”
Section: Pretreatment and Enzymatic Saccharificationmentioning
confidence: 99%
“…The approaches differ with regard to potential separation of the solid and liquid phases after pretreatment (Figure 1, Table 2). In some studies, the solids have been collected by centrifugation and thoroughly washed and neutralized with water and buffer [43,47,48,[54][55][56][57][58][59][60]71,73], while in other studies there has only been a neutralization step using concentrated buffer to adjust the pH prior to the enzymatic digestion step ( Table 2). Separation and washing is laborious, but the advantage is that more detailed information can be gathered from the experiment.…”
Section: Pretreatment and Enzymatic Saccharificationmentioning
confidence: 99%